GSM-based notification system and location tagging using GPS for smart recycle bin - Abd Wahab, Mohd Helmy; Obin, Nor Shilla; Ambar, Radzi; Tomari, Mohd Razali; Jabbar, Mohamad Hairol; Abdul Kadir, Aeslina (International Association of Computer Science and Information Technology, 2018)
This paper describe the design and development of a system to detect the level of recyclable waste in a smart recycle bin and then send notification signals including the locations coordinate to assist the authority to collect and empty the bin. At present, the current system does not provide a notification system mechanism to inform the waste authority that the recycle bin is full and need to be collected. Therefore, an automatic notification system is proposed as to reduce and optimize the collection time. This could also assist the waste collector to re-schedule the collection time and place depending on the regularity of the signal received. This could also reduce the manual collection process which require time and cost of labor. The development of the system involved the use of GSM module to enable the SMS text notification system and some software to manage all the notification received from the bin.